A reflective cycle: Understanding challenging situations in a school setting. Issue 1 (2nd January 2020) - Markkanen, Pihla; Välimäki, Maritta; Anttila, Minna; Kuuskorpi, Marko
ABSTRACT: Background : Good teacher–pupil relationships support the well-being of pupils and promote a good atmosphere in school settings. However, pupils' diverse needs and behavioural problems can cause challenging situations for teaching staff. There is currently limited understanding about the nature of these situations and how teachers respond and interact with pupils when these challenges arise. Purpose : The aim of this study is to explore the reflections of teaching staff on challenging situations with pupils, in order to gain insight into how teaching staff understand and conceptualise challenging situations. Sample, Design and Method : A descriptive qualitative study design was used. The data were collected from an online course aiming to support the skills that teaching staff employ when facing challenging situations with pupils. Participants were teaching staff who worked at a school in Finland. Qualitative data were derived from the reflective writings of these participants (teachers and classroom assistants, N = 10) about challenging situations. The participants structured their reflective writings using Gibbs' reflective cycle. Eight participants allowed us to use their writings as research data. The data analysis was a combination of deductive and inductive analysis. Results : Teaching staff were able to reflect on challenging situations from a variety of perspectives. Gibbs' reflective cycle was a helpful aid for teaching staff when reflecting on their feelings, thoughts, and actions related to challenging situations. The participants tried to understand the challenging situations from the pupils' point of view and considered the situations as opportunities to learn to review their professional practice. Conclusions : Teaching staff face challenging situations with pupils and have to meet the diverse needs of pupils constantly, in their everyday work. This small-scale study gives in-depth insight into teaching personnel's reflections on these situations. According to this study, the use of frameworks such as Gibbs' reflective cycle may help focus reflective learning gleaned from challenging experiences.